Peer-Assisted Learning in Undergraduate Midwifery Clinical Education: A Qualitative Study on Experiences of Nursing Students From Three Namibian Training Institutions - Kristine S Kandingu MSc; Vistolina Nuuyoma PhD (SAGE Open Nursing)
Introduction Peer-assisted learning is widely used in nursing education and is reported to have a positive impact on the students’ learning process. However, students’ experiences of peer-assisted learning from midwifery clinical education in resource-constrained, overcrowded, and small maternity sections are not documented. Objective This study was undertaken to explore undergraduate nursing students’ experiences of peer-assisted learning in midwifery clinical education context in Namibia. Methods The study was approached from a social constructivism, with explorative, descriptive, and contextual qualitative as a methodological approach. The sample consisted of 32 nursing students from three training institutions, who were conveniently sampled. Data collection was via five focus group discussions, which used a focus group discussion guide, audio recorder, and field notes as research instruments. Data were analyzed using thematic analysis. Results Main themes that emerged from thematic analysis are students’ conceptions of peer-assisted learning, benefits, challenges, and suggestions made to improve peer-assisted learning in midwifery clinical education. In thematic area of students’ conceptions of peer-assisted learning, peer teaching tools, engagement, care, and support of peers were recorded as subthemes. The benefits of peer-assisted learning included teamwork, professional identity, a deep approach to learning, communication, coping mechanisms, and socialization. Challenges experienced by students while using peer-assisted learning are learning wrong practices from peers, personality influence, discrimination, labeling, and name calling. Suggestions made by students were formalization and training of students on peer-assisted learning. Conclusions Students’ experiences of peer-assisted learning relate to how they understand it as a concept, their interaction with peers, and learning materials. In addition, students made suggestions to improve peer-assisted learning in midwifery clinical practice. These results may be useful in developing peer-assisted frameworks and guiding documents for use in its implementation in midwifery clinical education.